1984
DOI: 10.1135/cccc19841559
|View full text |Cite
|
Sign up to set email alerts
|

A convenient preparation of 1-CB11H12- and its C-amino derivatives

Abstract: Treatment of 7-(CH3)3N-7-CB10H12 with triethylamineborane(3) at 180-200 °C proceeds under splitting off one methyl group and inserting one boron vertex to obtain 1-(CH3)2NH-1-CB11H11. Methylation of the latter compound produces 1-(CH3)3N-1-CB11H11 which can be reduced to the parent 1-CB11H12- anion with sodium in liquid ammonia. The constitution of all compounds was established by NMR and mass spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(118 citation statements)
references
References 0 publications
1
114
0
Order By: Relevance
“…Carborane anions, [62][63][64] protonated arene salts, 45,58 and H9O4 + salts 27 were prepared as previously described. Solvents were dried by standard methods.…”
Section: Methodsmentioning
confidence: 99%
“…Carborane anions, [62][63][64] protonated arene salts, 45,58 and H9O4 + salts 27 were prepared as previously described. Solvents were dried by standard methods.…”
Section: Methodsmentioning
confidence: 99%
“…The IR spectrum shows very little perturbation of the CB 11 cluster bands relative to the silylium starting material so protonation of the anion must occur on the halogen substituents (red atoms X in Fig. 1) at the same positions (7)(8)(9)(10)(11)(12) …”
Section: Synthesis and Characterization Of Carborane Acidsmentioning
confidence: 99%
“…9 The chemistry of CB 11 H 12 2 lay fallow for a couple of decades while research on the neutral and dianionic isolectronic analogues, C 2 B 10 H 12 and B 12 H 12 22 , took precedence. In the mid-1980s, the dedicated Czech boron group of Plešek, Š tibr and Heřmá nek reported an improved synthesis from decaborane 10 and showed that halogenation proceeded quite selectively to give 7,8,9,10,11,12-hexahalogenated anions, CHB 11 H 5 X 6 2 (X 5 Cl, Br; see Fig. 1).…”
Section: Carborane Anionsmentioning
confidence: 99%
“…mercapto and dichloro dicarbanonaborates (Na-5-SH 7,8_C2-B9Hll ' Na-5,6-C12-C2-B9H10 ) belong to a new group of dicarbapolyborates synthesized by Plegek et al [13,14]. Dicarbanonaborates were dissolved in water and 1M solutions were stored at 0 ° C. During inhibition studies 2-20ram solutions were employed.…”
Section: Methodsmentioning
confidence: 99%